Reduction and Health Risk Assessment of Imidacloprid Insecticide Residues in Grapes Using Home Washing Methods - Parvaneh Shayanrad; Nasrin Hassanzadeh (Journal of Advances in Environmental Health Research)
Background: Grapes are one of the most important agricultural products in Malayer, and the pest Psalmocharias alhageos affects them. Imidacloprid, a systemic neonicotinoid insecticide, is commonly used to control pests. This study aims to assess the effectiveness of non-toxic household methods in reducing imidacloprid residues on grapes. Methods: The grape samples were collected from five different vineyards and immersed in various solutions (acetic acid, sodium bicarbonate, sodium chloride, detergents, and tap water). The QuEChERS method was used for pesticide residue extraction. Results: Washing treatments significantly reduced pesticide residues in the grapes. The reduction in imidacloprid residues varied, with sodium bicarbonate showing the highest reduction (50.41%), followed by acetic acid (30.03%), detergent (9.44%), sodium chloride (8.81%), and tap water (3.45%). The processing factors (PFs) after washing with these solutions were all less than 1, indicating that all treatments were effective in reducing imidacloprid residues. Conclusion: Imidacloprid residues were detected in all grape samples from the five vineyards. However, the imidacloprid concentrations after washing were below the CODEX maximum residue limit (MRL) (0.7 mg/kg). Health risk assessments indicated that consumers are not exposed to significant health risks from imidacloprid residues in grapes, with no serious side effects observed for adults, adolescents, or children.